2014
DOI: 10.1152/ajpheart.00332.2014
|View full text |Cite
|
Sign up to set email alerts
|

An afferent explanation for sexual dimorphism in the aortic baroreflex of rat

Abstract: Sex differences in baroreflex (BRx) function are well documented. Hormones likely contribute to this dimorphism, but many functional aspects remain unresolved. Our lab has been investigating a subset of vagal sensory neurons that constitute nearly 50% of the total population of myelinated aortic baroreceptors (BR) in female rats but less than 2% in male rats. Termed "Ah," this unique phenotype has many of the nonoverlapping electrophysiological properties and chemical sensitivities of both myelinated A-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 75 publications
(106 reference statements)
2
29
0
Order By: Relevance
“…This novel finding demonstrates that I h is a key player not only in cardiac pacemaking during phase 4 spontaneous depolarization but also in baroreflex discharge facilitating during afterhyperpolarization of afferent neurons. Moreover, the 17β-E 2 -mediated potentiation is confirmed in neither myelinated A-nor unmyelinated C-types, which may explain at least partially that 17β-E 2 leads a relatively lower firing threshold and higher discharge capability of Ah-type BRNs [4] and retains a lower blood pressure in ovary intact female rats compared with aged-matched males upon baroreflex [2]. The I h -dependent potentiation has advanced our understanding from a basic and physiologically relevant concept to practical applications potentially valuable for clinical and therapeutical conditions.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This novel finding demonstrates that I h is a key player not only in cardiac pacemaking during phase 4 spontaneous depolarization but also in baroreflex discharge facilitating during afterhyperpolarization of afferent neurons. Moreover, the 17β-E 2 -mediated potentiation is confirmed in neither myelinated A-nor unmyelinated C-types, which may explain at least partially that 17β-E 2 leads a relatively lower firing threshold and higher discharge capability of Ah-type BRNs [4] and retains a lower blood pressure in ovary intact female rats compared with aged-matched males upon baroreflex [2]. The I h -dependent potentiation has advanced our understanding from a basic and physiologically relevant concept to practical applications potentially valuable for clinical and therapeutical conditions.…”
mentioning
confidence: 90%
“…17β-Estradiol (17β-E 2 ), as a female hormone, demonstrates a boarder role in modulating neuroexcitability of visceral afferent neurons [1], such as baroreceptor neurons (BRNs), hence, participating in the baroreflex function [2], the cellular and ion channel mechanisms involved in this function have always attracted the keen attention of investigators. A wealth of information indicates that 17β-E 2 enhances the excitability in both CNS neurons [3] and visceral afferent neurons including BRNs [4] by modification of expression profiles of hyperpolarizationactivated cyclic nucleotide-gated (HCN) channels [5] underlying the funny current (I f ) or hyperpolarization-activated current (I h ), which is originally described in sinoatrial node myocytes as an inward current activated on hyperpolarization to the diastolic range of voltages and has the capability for generating repetitive activity [6].…”
mentioning
confidence: 99%
“…This experiment was conducted following the protocols described in details previously [13]. Briefly, 1.0-V and 15-V stimulus intensities were used to determine the fast (myelinated fiber activation, >2.0 M/s) and slow (unmyelinated fiber activation, <2.0 M/s) components of compound action potential (CAP), respectively.…”
Section: Electroneurogram (Eng)mentioning
confidence: 99%
“…This disorder occurs in five females for every one occurrence in males (Pickering (2002)). We speculate that this may be associated with different ratio of A- vs. Ah-fibers in males and females (see Li et al (2008); Chavez et al (2014)). …”
Section: Introductionmentioning
confidence: 98%
“…Another observation by Li et al (2008) from electrophysiological and anatomical studies in rats showed that A-type neurons may be separated into two subtypes A- and Ah-type, and that female rats have significantly more Ah-type neurons than male rats. Further studies by Chavez et al (2014) of these fibers have revealed that selective stimulation of myelinated neurons in female rats exhibits a lower threshold for MAP reduction compared to male rats suggesting that Ah-type baroreceptors may provide a functionally distinct afferent pathway within the baroreflex arc.…”
Section: Introductionmentioning
confidence: 99%